Early start of opicapone in Parkinson’s disease: evidence from a pooled analysis of phase 3 trials for sustained benefit in patients with recent onset of motor fluctuations - Ferreira, Joaquim J.; Stocchi, Fabrizio; Antonini, Angelo; Rascol, Olivier; Ebersbach, Georg; Kulisevsky, Jaime; Fonseca, Miguel M.; Ramos, Daniel; Rocha, José Francisco; Brigas, Helena C.; Holenz, Joerg; Poewe, Werner (Frontiers in Neurology, 2025)
BackgroundLevodopa is the mainstay of Parkinson’s disease (PD) therapy, but its long-term use is often complicated by the development of motor fluctuations. While COMT inhibitors, such as opicapone, are routinely used for managing motor fluctuations, recent evidence has suggested that earlier vs. later intervention, at onset of motor fluctuations, may provide greater benefits. However, the longer-term impact of earlier intervention has not been well studied.MethodsThis pooled subgroup analysis included data from randomized, 14–15 week, double-blind, placebo-controlled trials of opicapone and their 1-year open-label extensions. Exploratory analyses included all participants who were randomized to placebo or opicapone 50 mg, who continued opicapone into the open-label extension, and had developed motor fluctuations within 2 years before double-blind screening. Motor status was assessed using 24-h patient diaries and Unified Parkinson’s Disease Rating Scale (UPDRS) scores.ResultsThis post-hoc analysis included 227 patients who had been diagnosed with motor fluctuations within the prior 2 years (opicapone n = 117, placebo n = 110). Opicapone 50 mg significantly reduced daily OFF-time compared to placebo (mean placebo-adjusted reduction: –65.6 [95%CI, −105.5, −25.6] minutes, p = 0.0014) and increased Good ON-time (mean placebo-adjusted increase of: 88.3 [95% CI, 47.0, 129.6] minutes, p < 0.0001). Participants switching from double-blind placebo to open-label opicapone demonstrated the expected reductions in motor fluctuations. However, at the end of the open-label phase, those who started opicapone earlier maintained greater numeric reductions in OFF-time (mean treatment difference of −30.0 [95%CI, −74.8, 14.8] minutes, p = 0.2) and increases in total Good ON-time over 1 year (mean treatment difference of 38.2 [95%CI, −6.6, 82.9] minutes, p = 0.09) vs. those who switched from placebo. Mean levodopa doses remained stable throughout both the double-blind and open-label phases in both groups, indicating that the symptomatic benefits of opicapone were achieved without the need for increased levodopa dosing. There was no significant increase in troublesome dyskinesia.ConclusionEarly initiation of opicapone in PD patients with recently diagnosed motor fluctuations leads to sustained reductions in OFF-time and improvements in ON-time, without increasing dyskinesia or requiring escalation of levodopa doses. These exploratory findings support revising treatment strategies to include earlier use of opicapone, maximizing long-term benefits for patients with fluctuating PD.